2020
DOI: 10.1007/s10452-020-09814-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of native predators are more important than those of alien prey in determining the success of biotic resistance in marine systems

Abstract: Predator-driven biotic resistance is known to be more effective in marine systems than in terrestrial and freshwater environments. However, there is little consensus about when such resistance can be expected to succeed or fail. Here, we reviewed case studies that investigated interactions between native marine predators and alien prey, with the aim of establishing which characteristics are important in determining the outcome of such interactions. Four potential biotic resistance outcome scenarios were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…as a non-indigenous model concluding that various predators exert biotic resistance (Dumont et al 2011;Leclerc et al 2019;Giachetti et al 2020), we showed that in the native range of C. intestinalis, predation exerted by mobile generalist predators potentially leads to NIS facilitation. Thus, the issue of biotic resistance may depend more on the identity and characteristics of the considered native species, NIS and predator, rather than on the studied species status (NIS vs native; Skein et al 2020). Predictions on whether a NIS encounters resistance or facilitation by local predators in its introduced range could thus be formulated by looking at how various types of predation affect it in its native environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as a non-indigenous model concluding that various predators exert biotic resistance (Dumont et al 2011;Leclerc et al 2019;Giachetti et al 2020), we showed that in the native range of C. intestinalis, predation exerted by mobile generalist predators potentially leads to NIS facilitation. Thus, the issue of biotic resistance may depend more on the identity and characteristics of the considered native species, NIS and predator, rather than on the studied species status (NIS vs native; Skein et al 2020). Predictions on whether a NIS encounters resistance or facilitation by local predators in its introduced range could thus be formulated by looking at how various types of predation affect it in its native environment.…”
Section: Discussionmentioning
confidence: 99%
“…While still debated, these hypotheses provide a complex interplay of ideas in the context of predation and acknowledge its importance. Predation may be a key component in determining the success or failure of NIS (Keane and Crawley 2002;Cappuccino and Carpenter 2005;Joshi and Vrieling 2005;Skein et al 2020). Being predominantly tested in terrestrial habitats, few studies have been conducted on marine invasions often with inconsistent results with regard to these hypotheses (Chan and Briski 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This feeding behaviour increases the heterogeneity of fouling assemblages and can reduce the dominance of species, including NIS and cryptogenic species [30,91,92]. Due to this apparent lack of preference, S. cretense can play an important regulatory role in marine ecosystems, particularly in oceanic islands with relatively low diversity but high endemism [29,30,93,94]. Therefore, coastal ecosystems in oceanic islands exert lower biotic resistance against NIS than their counterparts in continental coastlines [95].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relatively tiny (20-30-mm) Scutellastra aphanes lives almost its entire live on shells of Perna perna (Robson, 1986) whereas the large (80-100 mm) S. argenvillei is largely excluded by dense beds of M. galloprovincialis (Steffani and Branch, 2003a;Steffani and Branch, 2003b;Steffani and Branch, 2003c;Branch and Steffani, 2004). Skein et al (2021) have broadened the consideration of characteristics that influence the invasion success of alien species to include features of both prey and predator. For prey, they list gregarious behaviour, high fecundity, high recruitment, dispersal potential and refuge from predation; for predators, preference for alien over native species, high feeding rate and high abundance feature.…”
Section: Effects Of Alien Species On Zonation Of S Granularismentioning
confidence: 99%